The Application of Virtual Reality (VR) in the Contemporary Dance Work “Sabitah Eternity” - Dwi Prakasa, M Aqsal; Novalinda, Sherli; Sukri, Ali (Pascasarjana Institut Seni Indonesia Padang Panjang, 2024)
Penerapan Virtual Reality (Vr) dalam Karya Tari Kontemporer “ Sabitah Eternity ” SABITAH ETERNITY's work is a dance work that tries to be a bridge to connect education to the audience watching this work. The aim is to increase theaudience's sense of empathy and social towards those who are trying to adapt to an era that is often considered an issue that until now is still not very popular. is heavily questioned as a complicated social phenomenon, in this case the Talang Mamak tribe and its Bedukun Balai Terbang treatment rituals. The artist tries to convey how the Talang Mamak people and their healing rituals can go through various situations and conditions towards modern times and adapt in it. This is for the sake of the continuity of culture and community groups, as well asphase of change and response of the Bedukun Balai Terbang ritual performers. In this case the negotiating body of tribal society towards the present era. The use of expression and technology as a medium of communication means that we never know what everyone is feeling. The use of Virtual Reality technology is something new in a form of dance performance that conveys a lot of the content that the artist wants to convey. ABSTRAKKarya SABITAH ETERNITY salah satu karya tari yang mencoba menjadi jembatan penyambung edukasi terhadap audience yang menyaksikan pertunjukan karya ini, bertujuan agar dapat meningkatkan rasa empati dan sosial penonton terhadapmereka yang sedang mencoba beradaptasi dengan zaman yang sering dianggap sebagai isu yang sampai saat ini masih tidakterlalu gencar dipermasalahkan sebagai fenomena sosial yang rumit, dalam hal ini suku Talang Mamak dan ritualpengobatan Bedukun Balai Terbangnya. Pengkarya mencoba menyampaikan bagaimana masyarakat Talang Mamak dan ritual pengobatannya dapat melewati berbagai situasi dan kondisi menuju masa modern dan beradaptasi di dalamnya. Hal itu demi keberlangsungan budaya dan kelompok masyarakatnya, serta fase perubahan dan respon pelaku ritual BedukunBalai Terbang. Dalam hal ini negosiasi tubuh masyarakat suku terhadap era sekarang. Penggunaan ekspresi dan teknologisebagai media komunikasi, bahwa kita tidak pernah tau apa yang dirasakan setiap orang. Penggunaan teknologi Virtual Reality menjadi suatu hal baru dalam suatu bentuk pertunjukan tari yang banyak menyampaikan isi yang ingin disampaikan pengkarya.